THE INFLUENCE OF ACTIVE LEARNING MODELS ON THE LEARNING OUTCOMES OF PGSD STUDENTS IN SEMESTER 2 - Paduppai, Andi Mardiana; Fitrawantono, Marsheyla Resty; Widiya, Nur (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to explore the impact of active learning models on student learning outcomes in the PGSD Study Program in semester 2 using a qualitative approach. Method: The method chosen was a qualitative survey through an open-ended questionnaire, combined with a phenomenological approach to deeply understand students' personal experiences of active learning. A total of 79 respondents participated in this study. Data were analyzed by thematic analysis to find meaning and patterns in the learning experience. Result: The results showed that the active learning model had a positive impact on increasing students' participation, understanding of the material, and sense of responsibility for learning. Students feel more cognitively and affectively fulfilled, and can connect learning with real-world experiences. Novelty: The findings confirm the importance of andragogy principles in higher education, where students as adult learners benefit more from participatory and reflective learning processes.